Effect of Fluoride-Ion on the Electrochemical Behavior of Tantalum Ion in NaCl-KCl Molten Salt. Issue 8 (1st August 2022) - Bai, Xuyang; Li, Shaolong; He, Jilin; Song, Jianxun
Abstract : In the process of molten salt electrolysis, the influence of the composition of the electrolyte on the current efficiency and electrolysis quality is a key issue that needs to be studied urgently. Thus, the interaction between tantalum ions and anions, coordination competition between chlorine ions and fluoride ions in the electrochemical metallurgy of tantalum metal are investigated in this paper. Their effects on the reduction mechanism of tantalum ions was also studied. Moreover, the chemical coordination mechanism of tantalum ions in the above molten salts were revealed through electrochemical tests and chemical analysis. By adding fluoride ions, the reduction step of tantalum ions is reduced from two-step to one-step, which simplifies the reduction process, avoids the current empty consumption caused by the disproportionation reaction of low-valent tantalum ions, and optimizes the particle size of the product.